Heterogeneous conversion of COF2 to HF in polar stratospheric clouds - Wofsy, Steven C.; Yatteau, John H.; Salawitch, Ross J.; Mcelroy, Michael B.; Toon, Geoffrey C. (1990)
It is argued that the reaction COF2 + H2O - 2HF + CO2 should proceed on surfaces of polar stratospheric clouds, based on laboratory evidence for this reaction in condensed phase and on analysis of column observations of HF during the Airborne Arctic Stratospheric Expedition. If the hypothesis is confirmed, observations of COF2 and HF could provide unambiguous indication of heterogeneous processing of polar air, and could help elucidate the influence of heterogeneous chemistry on concentrations of HCl, ClNO3, and chlorine oxide radicals.